Hadith #3709 - Sunan Abi Dawud - Abdullah bin al-Dayli; Abu 'Amr al-Saybani أبو عمرو السيباني; Dmrh bin Rabi'ya al-Flstyny ضمرة بن ربيعة الفلسطيني أبو عبد الله; Fyrwz al-Dylmy (Sunan Abi Dawud)
I am afraid it may not be muzza from which(the people of) ‘Abd al-Qais were prohibited. I asked Qatadah : What is muzza’? He replied: Drink of dates made in a green jar and vessels smeared with pitch.
Grade: Da'if

Hadith #4300 - Sunan Abi Dawud - Abu 'Amr al-Saybani أبو عمرو السيباني; Dmrh bin Rabi'ya al-Flstyny ضمرة بن ربيعة الفلسطيني أبو عبد الله; Isa bin Muhammad bin al-Nahas عيسى بن محمد بن النحاس (Sunan Abi Dawud)
Salah is near Khaibar.
Grade: Sahih

Hadith #4320 - Sunan Abi Dawud - Abu 'Amr al-Saybani أبو عمرو السيباني; Abu Umama bin Sahl; Dmrh bin Rabi'ya al-Flstyny ضمرة بن ربيعة الفلسطيني أبو عبد الله (Sunan Abi Dawud)
The Prophet (ﷺ) said: I have told you so much about the Dajjal (Antichrist) that I am afraid you may not understand. The Antichrist is short, hen-toed, woolly-haired, one-eyed, an eye-sightless, and neither protruding nor deep-seated. If you are confused about him, know that your Lord is not one-eyed. Abu Dawud said: ‘Amr bin Al-Aswad was appointed a judge.
Grade: Sahih